Through a glass darkly [videorecording (DVD)] - Bergman, Ingmar, 1918-2007; Andersson, Harriet; Björnstrand, Gunnar, 1909-1986; Sydow, Max von, 1929-2020-; Passgård, Lars, 1941-2003 (Criterion collection, 2003)
"While vacationing on a remote island retreat, a family's already fragile ties are tested when Karin discovers her father has been using her schizophrenia for his own literary means. As she drifts in and out of lucidity, her father, husband, and younger brother are unable to prevent Karin's harrowing descent into the abyss of mental illness."--Container.